Analisis Keberlanjutan Usaha Sayuran Hidroponik (Studi Kasus Griya Hijau Hidroponik Kota Bandung) - Nazhifa, Rifda; Kusumo, Rani Andriani Budi (Universitas Galuh, 2026)
This study aims to analyze the sustainability of hydroponic vegetable farming through a case study at Griya Hijau Hidroponik in Bandung City. The research uses a qualitative approach with a case study method to deeply understand how sustainability is practiced across economic, social, and ecological dimensions based on the Triple Bottom Line framework and Global Reporting Initiative (GRI) indicators. Data were collected through in-depth interviews, direct observations, and documentation, with key informants including business actors, partners, and local stakeholders.The findings reveal that the economic sustainability of the business is reflected in stable operations and a positive Return on Investment (ROI), although profitability remains limited. Socially, the business has successfully built strong partnerships with the community, local government, and distribution networks, and actively engages in community empowerment. Ecologically, Griya Hijau Hidroponik implements environmentally friendly practices, including water efficiency, organic waste management, and the use of reusable growing media.It can be concluded that Griya Hijau Hidroponik is socially and ecologically sustainable and is able to endure in the long term despite limited economic profits. This research is expected to serve as a reference for the development of sustainable urban agriculture in Indonesia.